UV-HPLC METHOD DEVELOPMENT AND VALIDATION FOR QUANTIFICATION OF BESIFLOXACIN HYDROCHLORIDE - Saha, Bijit; Patel, Rakesh P; Halder, Tripti (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The objective of the present investigation was to develope and validates a new, rapid, accurate high performance liquid chromatographic (HPLC) method for the quantification of Besifloxacin Hydrochloride. Methods: Isocratic UV-HPLC separation was performed using a Zodiac C18 (150 X 4.6 mm) column, with 150 volume of Acetonitrile and 350 mL of Methanol in 500 mL buffer as mobile phase at a flow rate of 2 mL/min and UV detection at 295nm.. Results: The sample found stable for 24 hours in analyte solution and compatible with nylon filter. The Beer’s law plots were found to be linear over the concentration range 70% to 130% with a correlation coefficient (r2) 0.9999 in diluent, phosphate buffer and simulated tear media. The %RSD was found less than 2% shows good precision, acceptable accuracy and reproducibility of the new method for the determination of Besifloxacin Hydrochloride. Conclusion: The method was validated as per the ICH guidelines. The method is accurate and can be applied for qualitative analysis of Besifloxacin Hydrochloride in bulk drug and in formulation. Â